The Effect of Using Markov Chains in the Planning of University Education "An Applied Study on the Community College for Girls in Khamis Mushait" - Abdullah, Suhad (Arab Journal for Sciences and Research Publishing, 2017)
The study dealt with the problem of the low number of graduates from Khamis Mushait College compared with the number of college graduates every year. It was necessary to know why the number of female graduates in college was low. Each year, based on statistics available to female students in the community college in Khamis Mushait, the researcher had to reach the problem of the study by answering the following questions: What is the average time remaining for students at each level in Khamis Mushait College? Probability of female students graduated from college? What is the probability of leakage (separation) student from the college? What is the average number of students expected to graduate during the years of the study? What is the average number of students expected to separate them during the years of the study? Through this we devoted this study to calculate the duration of female students in the college in their departments. This study deals with the use of Markov series as a method of random operations. This method is one of the best methods used in analyzing the numbers of female students during the study, as well as estimating the time required for students to graduate, in order to link the outputs of education with the needs of society. The study also dealt with the literature of the study and the practical side of the series Markov and then applied to the data of students of the Community College for Girls Khamis Mushait - King Khalid University during the period from 1434 to 1436 e, and the study has reached several results, the most important of which: 1- The number of graduates in each department not corresponds to the number of female students in K L section. 2 - Graduation rate in the three sections indicate that the number of graduates is weak. 3 - Application of the model can be said that this model is highly efficient and its ability to estimate the number of graduates are high where the results are very close to reality. The study recommends several recommendations, the most important of which are: 1 - We recommend applying this study to other educational outputs such as the number of professors and their degrees and the budget of professors, 2 - We recommend solving the problems of departments by the administration of the college and the university to obtain the best methods of teaching which may increase the proportion of female graduates.
Keywords: Markov Chains; Planning; University Education